The political economy of China’s transition - Fewsmith, J (Foundation for Law, Justice and Society, 2007)
This policy brief argues that Minxin Pei’s China’s Trapped Transition: The Limits of Developmental Autocracy contains a number of useful insights into the political economy of contemporary China. These include recognition of the convergence of the economic and political elite in ways that tend to perpetuate the dominance of that elite; recognition that economic development can strengthen autocracy, by providing greater resources for the state both to repress societal challenges and distribute patronage; and recognition that this pattern of rule has created a number of governance deficits that have distorted China’s socio-economic growth causing a serious erosion of social justice.